Single-cell multiomics and chromatin structure reveal gene-regulatory dynamics in heart failure - Yang Xie; Luca Tucciarone; Elie N. Farah; Lei Chang; Qian Yang; Thirupura S. Shankar; Weston Elison; Shaina Tran; Jovina Djulamsah; Audrey Lie; Timothy Loe; Alyssa R. Holman; et al. (Science, 2026)
Heart failure is a leading cause of morbidity and mortality, yet gene-regulatory mechanisms driving cell type–specific pathologic responses remain undefined. Here, we present the cell type–resolved transcriptomes, chromatin accessibility, histone modifications, and chromatin organization of 13 nonfailing and 23 failing human hearts across all cardiac chambers. Integrative analyses revealed dynamic changes in cell type composition, gene-regulatory programs, and chromatin organization, particularly in cardiomyocytes and fibroblasts. Mapping cell type–specific enhancer-gene interactions from these analyses enabled the illumination of likely causal genetic contributors to heart failure from genetic association data. Together, these findings provide multimodal gene-regulatory maps of the human heart in health and disease, offering a framework for designing precise, cell type–targeted therapies for treating heart failure.